ANALYSIS VIEW LIFE AND IDEALISM AUTHOR IN SHORT STORY "WHEN MAS GAGAH WENT" BY HELVY TIANA ROSA WITH AN EXPRESSIVE APPROACH - Yudianto; Titin Nurhayatin; Rani Siti Fitriani (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Study This aiming For analyze view life And idealism author in the short story "When Mas Gagah Left" by Helvy Tiana Rosa with an expressive approach. This study explores the philosophical underpinnings and thematic elements that reflect the author's perspective on life, society, and personal values. Using an expressive approach, this study highlights how the author's emotions and experiences shape the narrative and character development in the story. The findings show that the author's outlook on life is strongly influenced by the cultural and social context, which are closely interwoven. in structure narrative. Analysis This No only contribute on understanding Which more deeply into Helvy Tiana Rosa's literary work, but also offers insight into the broader implications of her idealism in contemporary society.